Exploring Psychological Resilience Factors in Coping with Uncertainty and Rapid Social Changes in Contemporary Society - Lodiana Ayu; Andreas Agung Kristanto; Abdul Aziz; Makmur Solahudin; Sefi Ernawati (Mandalika Institute, 2026)
Psychological resilience has become an essential construct in understanding how individuals adapt to increasing levels of uncertainty and rapid social transformation in contemporary society. However, existing literature remains fragmented in explaining how cognitive, emotional, and social mechanisms interact under conditions of chronic uncertainty. This study presents an exploratory systematic thematic literature review of Scopus-indexed open-access studies focusing on psychological resilience, cognitive flexibility, ambiguity tolerance, emotional regulation, and social support. The analysis identifies three core resilience factors: cognitive mechanisms (cognitive flexibility, ambiguity tolerance, and meaning-making), emotional mechanisms (emotion regulation, optimism, and self-efficacy), and social-contextual mechanisms (social support, community belonging, and access to resources). Findings indicate that resilience is not a static trait but a dynamic and interactive system shaped by continuous adaptation processes. The study contributes to resilience theory by extending classical models toward a process-oriented and context-dependent framework suitable for contemporary social uncertainty.